Internationalising the University 2009
DOI: 10.1057/9780230235007_11
|View full text |Cite
|
Sign up to set email alerts
|

Building on Experience: Meeting the Needs of Chinese Students in British Higher Education

Abstract: Chinese students now form a large proportion of international students in the universities of the English-speaking world. Competition between the 'inner-circle' English-speaking countries (Australia, Canada, the UK and USA) is fierce with all the major players expressing concern about the effectiveness of their recruitment efforts. Based on the experiences of a wide range of university teachers and administrators in the UK, this report explores issues in providing effective higher education for students from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 10 publications
(11 reference statements)
1
55
0
Order By: Relevance
“…Most studies in the field focus almost exclusively on Chinese students' choices and experiences in English-speaking countries, e.g. the UK, Australia, New Zealand and the U.S. (Altbach, 2004;Sin, 2009;McMahon, 2011;Simpson et al, 2010;Fernandes, 2007;Burnett and Gardner, 2006;Edwards and Ran, 2006;Turner, 2006;Ridley, 2004) but there has been relatively little research to date on the educational and socio-cultural experiences of Chinese students who study at British university campuses located outside the 5 UK (with the notable exception of Leung and Waters, 2013). There is, however, a growing literature on international students' experiences of cultures other than their own, including Chinese students' experience of British universities (see Spencer-Oatey and Xiong, 2006;Gu and Schweisfurth, 2010;Schweisfurth and Gu, 2009;Gu, Schweisfurth and Day, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in the field focus almost exclusively on Chinese students' choices and experiences in English-speaking countries, e.g. the UK, Australia, New Zealand and the U.S. (Altbach, 2004;Sin, 2009;McMahon, 2011;Simpson et al, 2010;Fernandes, 2007;Burnett and Gardner, 2006;Edwards and Ran, 2006;Turner, 2006;Ridley, 2004) but there has been relatively little research to date on the educational and socio-cultural experiences of Chinese students who study at British university campuses located outside the 5 UK (with the notable exception of Leung and Waters, 2013). There is, however, a growing literature on international students' experiences of cultures other than their own, including Chinese students' experience of British universities (see Spencer-Oatey and Xiong, 2006;Gu and Schweisfurth, 2010;Schweisfurth and Gu, 2009;Gu, Schweisfurth and Day, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many British scholars have investigated and reported the difficulties Chinese students face in their daily and academic life (Cortazzi and Jin, 1997;Edwards and Ran, 2006;Edwards et al, 2007;Liu, 2009;Spencer-Oatey and Xiong, 2006). In these investigations, academic matters such as understanding lectures, adapting study skills and studentteacher relationships have been identified as the biggest source of difficulty for Chinese students.…”
Section: Chinese Students' Experiences Of Humor In Britainmentioning
confidence: 99%
“…In these investigations, academic matters such as understanding lectures, adapting study skills and studentteacher relationships have been identified as the biggest source of difficulty for Chinese students. Another repeatedly reported issue regarding Chinese students in Britain is that they experience much less intercultural interaction with native speakers than they expect (Edwards and Ran, 2006;Gu, 2009;Robson and Turner, 2007;Spencer-Oatey and Xiong, 2006;Tian and Lowe, 2009). …”
Section: Chinese Students' Experiences Of Humor In Britainmentioning
confidence: 99%
“…Commonly identified academic issues that international students (and in particular Chinese students) encounter include becoming accustomed to western notions of student-teacher relationships, implementing self-learning strategies, engaging in team work and group assessments, dealing with language issues, academic writing and plagiarism (Edwards and Ran, 2006;Akoudis and Tran, 2010). Language and learning support programs are largely available in Australian universities (Robertson et al, 2000;Ramburuth and McCormick, 2001;Andrade, 2006).…”
Section: Support For International Studentsmentioning
confidence: 99%